Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Express the given function:

[tex]\[ y = 2x^3 - 3x^2 + 6x \][/tex]


Sagot :

Certainly! Let's write a detailed, step-by-step solution for the given equation [tex]\( y = 2x^3 - 3x^2 + 6x \)[/tex].

### Step 1: Understanding the Problem
You are given a polynomial equation:
[tex]\[ y = 2x^3 - 3x^2 + 6x \][/tex]

### Step 2: Identify the Terms
The given polynomial is of the third degree (cubic equation), and it consists of the following terms:
- [tex]\( 2x^3 \)[/tex] (cubic term)
- [tex]\( -3x^2 \)[/tex] (quadratic term)
- [tex]\( 6x \)[/tex] (linear term)

### Step 3: Derivatives (If Asked for Slope or Critical Points)
If the task is to find the first derivative [tex]\( \frac{dy}{dx} \)[/tex], which represents the slope of the tangent line to the curve at any point [tex]\( x \)[/tex], it would involve differentiating each term individually.

The first derivative [tex]\( \frac{dy}{dx} \)[/tex] will be:
[tex]\[ \frac{dy}{dx} = \frac{d}{dx}(2x^3) - \frac{d}{dx}(3x^2) + \frac{d}{dx}(6x) \][/tex]

By applying the power rule [tex]\( \frac{d}{dx}(x^n) = n*x^{n-1} \)[/tex]:
[tex]\[ \frac{dy}{dx} = 6x^2 - 6x + 6 \][/tex]

### Step 4: Evaluating [tex]\(y\)[/tex] at Specific Points (If Asked)
To find the value of [tex]\(y\)[/tex] at a specific [tex]\(x\)[/tex], substitute that value of [tex]\(x\)[/tex] into the equation. For example:
- If [tex]\( x = 1 \)[/tex]:

[tex]\[ y = 2(1)^3 - 3(1)^2 + 6(1) = 2 - 3 + 6 = 5 \][/tex]

- If [tex]\( x = 0 \)[/tex]:

[tex]\[ y = 2(0)^3 - 3(0)^2 + 6(0) = 0 \][/tex]

### Step 5: Critical Points (If Asked for Extrema)
To find critical points, set the first derivative to zero and solve for [tex]\(x\)[/tex]:
[tex]\[ 6x^2 - 6x + 6 = 0 \][/tex]

Since we recognize this as a quadratic equation, solve using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex]:

Here, [tex]\( a = 6 \)[/tex], [tex]\( b = -6 \)[/tex], and [tex]\( c = 6 \)[/tex]:
[tex]\[ x = \frac{6 \pm \sqrt{(-6)^2 - 4(6)(6)}}{2(6)} \][/tex]
[tex]\[ x = \frac{6 \pm \sqrt{36 - 144}}{12} \][/tex]
[tex]\[ x = \frac{6 \pm \sqrt{-108}}{12} \][/tex]

Since the discriminant ([tex]\( -108 \)[/tex]) is negative, there are no real roots, meaning the equation [tex]\( 6x^2 - 6x + 6 = 0 \)[/tex] does not have real solutions, and hence no critical points derived from real solutions.

### Step 6: Understanding the Shape of the Curve
To determine the behavior of the polynomial [tex]\( y = 2x^3 - 3x^2 + 6x \)[/tex]:
- As [tex]\( x \to \infty \)[/tex], the [tex]\( 2x^3 \)[/tex] term dominates, so [tex]\( y \to \infty \)[/tex].
- As [tex]\( x \to -\infty \)[/tex], the [tex]\( 2x^3 \)[/tex] term again dominates, so [tex]\( y \to -\infty \)[/tex].

### Conclusion
The curve described by the equation [tex]\( y = 2x^3 - 3x^2 + 6x \)[/tex] is a cubic polynomial with no real critical points from the first derivative and trends to [tex]\( \infty \)[/tex] as [tex]\( x \to \infty \)[/tex] and to [tex]\( -\infty \)[/tex] as [tex]\( x \to -\infty \)[/tex]. For any specific [tex]\( x \)[/tex], you can substitute it into the polynomial to find the corresponding [tex]\( y \)[/tex]-value.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.